Environmental Management Practices within Agritourism Boarding Houses in Romania: AQualitative Study Among Managers - Ana Ispas; Elena-Nicoleta Untaru; Adina Candrea (My University, 2019)
Small accommodation businesses such as agritourism boarding houses (ATBHs) provide a largeshareofaccommodatingcapacityincertainruraldestinations.Despitetheirsmallaccommodation capacity, ATBHs consume substantial quantities of water and energy; this consumption implies high environmental costs. The present study aims to explore opinions of ATBH owner-managers regarding water and energy consumption in their businesses, what motivates them to adopt environmental practices, and the specific saving measures used within the tourist accommodation units they manage. Aqualitative research was conducted, using semi-structured interviews among 12 Romanian ATBH owner-managers. Data analysis revealed that the interviewed owner-managers understand the importance of natural resource conservation in tourist destinations but they are not willing or have insu cient financial, time, organizational resources, etc. to engage in serious water and energy saving initiatives. Moreover, most interviewed managers indicated that tourists cannot make a significant contribution to natural resources conservation in accommodation units and perceive water and energy saving systems as more e ective than the environmental education of visitors in their facility. These findings may be useful to tourism policy-makers and environmental organizations in order to develop e ective environmental strategies in ATBHs.
Keywords: environmental management; agritourism boarding houses; rural tourism; water; energy; resource saving